Entre Marx et Bakounine : César De Paepe : correspondance - Marx, Karl; Bakoenin, Michail; De Paepe, César; Dandois, Bernard (Paris : Maspero, 1974)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: Eerste Internationale (1864-1876).; Marx, Karl; Bakoenin, Michael; communisme; utopisme